Appraisal of the validity and reliability of the young parenting inventory (YPI-R3) in a sample of Iranian adolescents - Esmaeil Farshbaf Khoshnazar; Mohammad Reza Shairi; Mohsen Kachooei; Hojjatollah Farahani (مجله علوم روانشناختی)
Background: Adverse childhood experiences wield a significant and enduring impact on long-term health and well-being, closely intertwining with the development of early maladaptive schemas. To meticulously explore the role of parent-child relationships in this dynamic, the Young Parenting Questionnaire underwent iterative design and refinement across subsequent versions. Aims: This study aimed to ascertain the validity and reliability of the third iteration of the Young Parenting Questionnaire within a sample drawn from the 18-16 community in Tehran. Methods: Employing a descriptive survey approach, the study encompassed 922 high school students from various districts of Tehran. Convergent and divergent validity were assessed through multiple instruments, including measures of parental acceptance-rejection, attachment to parents and peers, depression, anxiety, stress, internal shame, psychological well-being, and gratitude. Reliability was evaluated using Cronbach's alpha coefficient, omega coefficient, inter-item correlation, and test-retest reliability. Results: The Young Parenting Questionnaire exhibited positive correlations with measures of parental acceptance and rejection, attachment to parents and peers, internal shame, and symptoms of depression, anxiety, and stress as assessed by the DASS questionnaire. Conversely, it displayed a negative correlation with psychological well-being and gratitude measures. Cronbach's alpha coefficients for questions pertaining to fathers and mothers were reported as 0.94 and 0.93, respectively. Test-retest reliability demonstrated a correlation coefficient of 0.92 (p< 0.01), indicating temporal stability. Conclusion: The third iteration of the Young Parenting Questionnaire demonstrated robust validity and reliability. Consequently, it can be cautiously employed in both research endeavors involving adolescents and clinical settings pertaining to adolescent issues. Nonetheless, further research endeavors should address the current study's limitations to offer a more comprehensive understanding of the questionnaire's applicability within Iranian society.